2002
DOI: 10.1007/s10096-002-0798-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Characteristics of Infective Endocarditis When Associated with Spondylodiscitis

Abstract: Spondylodiscitis is rarely observed in association with infective endocarditis (IE). In the study presented here, 92 cases of definite IE were examined. Spondylodiscitis was present in 14 (15%) cases. The mean age of patients with spondylodiscitis was 69.1+/-13.6 years (range, 33-87 years). The male-to-female ratio was 8:6. Predisposing heart disease was found in nine (64.3%) cases. Back pain was reported in all cases. Spondylodiscitis was diagnosed before endocarditis in all cases. The infection affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 19 publications
1
41
1
4
Order By: Relevance
“…The first was reported by Sèze et al [8]. Le Moal et al [9] reported that the prevalence of spondylodiscitis in patients with IE was of 15%. Spondylodiscitis, has rarely been described, particularly in case reports.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The first was reported by Sèze et al [8]. Le Moal et al [9] reported that the prevalence of spondylodiscitis in patients with IE was of 15%. Spondylodiscitis, has rarely been described, particularly in case reports.…”
Section: Discussionmentioning
confidence: 88%
“…A careful review of the patient's history and physical examination, as well as laboratory data and diagnostic imaging studies are necessary. Musculoskeletal symptoms can represent the major sign of the disease, leading to diagnostic difficulties [9].…”
Section: Discussionmentioning
confidence: 99%
“…Le Moal et al 12 reported that the prevalence of spondylodiscitis in patients with IE was of 15%. Spondylodiscitis, however, has rarely been described, partic- Spondylodiscitis and endocarditis caused by S. vestibularis ularly in case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the patient presents with decreased range of motion and spinal tenderness. 12 As regards the pathogenesis, some authors have suggested that back pain is due to microemboli of immune complexes with or without bacteria. 15 The lumbar region is most commonly involved (60%), and thoracic spine can also be affected (26%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation